2018
DOI: 10.1007/s00429-018-1711-4
|View full text |Cite
|
Sign up to set email alerts
|

Bradykinin B2 receptor is essential to running-induced cell proliferation in the adult mouse hippocampus

Abstract: Physical exercise is a strong external effector that induces precursor cell proliferation in the adult mouse hippocampus. Research into mechanisms has focused on central changes within the hippocampus and we have established that serotonin is the signaling factor that transduces physical activity into adult neurogenesis. Less focus has been given on potential peripheral signals that may cause pro-mitotic running effects. Vasoactive kinin peptides are important for blood pressure regulation and inflammatory pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Alternatively, exercise could enhance synaptogenesis of OFF cell projections in the spinal cord, purported to inhibit nociception, which would result in a lower proportion of ON-cells. In support, there is a substantial body of literature showing cell proliferation, increased synaptic densities, and synaptogenesis in the hippocampus after exercise [64][65][66]. For example, in the hippocampus, blockade of mu-opioid receptors reduces exercise-induced synaptogenesis suggesting endogenous opioids can promote synaptogenesis [47].…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, exercise could enhance synaptogenesis of OFF cell projections in the spinal cord, purported to inhibit nociception, which would result in a lower proportion of ON-cells. In support, there is a substantial body of literature showing cell proliferation, increased synaptic densities, and synaptogenesis in the hippocampus after exercise [64][65][66]. For example, in the hippocampus, blockade of mu-opioid receptors reduces exercise-induced synaptogenesis suggesting endogenous opioids can promote synaptogenesis [47].…”
Section: Discussionmentioning
confidence: 99%
“…Those results point out to an inhibition of the gluconeogenesis, and were confirmed by the slightly increased AKT phosphorylation observed in the Western blot analysis, which is also consistent with the hyperinsulinemia caused by CAF. AKT phosphorylation is a central intracellular action caused by the insulin signaling [ 26 ]. Phosphorylated AKT phosphorylates FoxO1 cause its exclusion from the nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…Specific primer sequences for the genes encoding glucose-6-phosphatase, glucokinase, phosphoenolpyruvate, carboxykinase, fructose 1,6-bisphosphatase, and hepatocyte nuclear factor 4-alpha were designed and tested in the samples by analyzing the curve patterns, in order to set the amplification effectiveness of each primer pair. For the Kinin B2 receptor expression Quantitative PCR was performed with the TaqMan system (Applied Biosystems, Carlsbad, CA) and specific kit of oligonucleotides (B2R-Forward- , B2R-Reverse- , the control gene was the Glyceraldehyde-3-phosphate dehydrogenase (GadDH)—Forward- and Reverse- ) [ 26 ], and the thermic protocol was as follows: holding 95°C for 10 min, and a cycle of 95°C for 30 s, 60°C for 30 s, and 72°C for 30 s repeated 40 times. Gene expression was normalized against the GadDH gene expression and defined as relative values utilizing the threshold cycle method (CT; 2-ΔΔCt), following instructions from the manufacturer [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Many studies have shown that environmental enrichment including voluntary exercise and somatomotor and visuospatial stimulation is capable of promoting the modulation of cytokines (Pedersen, 2009) and chemokines (Trøseid et al, 2004), natural killer cells (Benaroya‐Milshtein et al, 2004), and T lymphocytes mobilization (Marashi, Barnekow, Ossendorf, & Sachser, 2003; de Sousa et al, 2011; Singhal et al, 2020), microglia (Gomes et al., 2019; de Sousa et al., 2015) and astrocytes numerical and morphological changes (Diniz et al, 2010; Diniz, Silva, et al, 2016; Leardini‐Tristão et al, 2020; Singhal et al, 2020) and neurogenesis (Valero, Paris, & Sierra, 2016; Wasinski, Batista, Bader, Araujo, & Klempin, 2018). Bi‐directional cross talk between microglia, astrocytes and neurons (Singhal et al, 2020; Kofuji & Araque, 2020) are key elements to achieve homeostatic conditions, and chemokine signaling seems to be essential to orchestrate communication among them, preserving brain function (Trettel, Di Castro, & Limatola, 2019).…”
Section: Discussionmentioning
confidence: 99%